Ентропія в діяльності підприємства: суть та основні підходи до оцінювання - Дейнега, О. В.; Дейнега, І. О. (Видавництво Львівської політехніки, 2018)
Ідентифіковано області застосування поняття “ентропія” та його суть. Визначено умови виникнення ентропії в економіці. Ідентифіковано специфічні особливості прояву економічної ентропії. Систематизовано складові, розглянуто основні підходи до оцінювання, сформовано перелік факторів впливу на ентропію, що виникає у діяльності підприємств. Наведено заходи, що сприяють зниженню рівня ентропії у практиці господарювання підприємств. Встановлено, що найвагомішим фактором, що визначає ринкову успішність підприємства, як економічної системи, є доступність до якісної інформації.

The phenomenon of entropy is studied in completely different areas, where it is considered one of the main philosophical concepts and unique physical. Economic entropy is the most difficult to study with its kind, since economic processes are multifaceted and interact with numerous processes of different types of systems (biological, technical, etc.). Such an entropy implies not only the loss of the intensity of the motion of matter, but also the loss of the results of human activity, which are symbiotic in nature. The current uncertainty leaves all possible future consequences of management decisions that are not known, and the events that are actually happening are unknown in advance. As a result, there are risks that determine the most commonly used probability calculation, which will provide a solid basis for management, as a technological process, analysis of the costs of the production system and the usefulness of market information. That is why assessing the level of negentropy of the enterprise environment and identifying possible factors of influence on it, and, hence, the possibility of developing and implementing effective management decisions that will contribute to its reduction, is an important task of management that needs urgent solution. In the practice of managing the enterprises to reduce the level of uncertainty necessary for the adoption of economic decisions may occur due to the implementation of such measures: the holding of information collection that reduces the uncertainty of expectations; processing of information by various methods (including analysis, forecast, scenario), which allows to raise the level of its quality and clarify the causes, forms and effects of uncertainty; developing models that are adequate to existing situations, and obtaining as a result of modeling the values of target values, functional dependencies of the state of the control object and the environment. Objective assessment of the entropy of the enterprise requires a comprehensive approach, which should take into account the so-called internal environment of the enterprise. The state of the internal entropy of the enterprise will greatly depend on the qualifications, work experience, and the level of education of employees, which can be summarized in such a indicator as a “thesaurus”. It is necessary to distinguish between the individual thesaurus of the user of information (a separate employee) and the collective thesaurus of the enterprise, which will be defined as a set of individual thesauri. As an indicator of assurance in decisionmaking, it is proposed to use a coefficient of determiniseness of the environment or negentropy, which will take into account the quality and degree of importance of the information used, as well as the level of the collective thesaurus of the enterprise. All marketing indicators, including the most accurate estimates of the market capacity and the share of the company, obtained as a result of marketing research, should be adjusted to this ratio.
Entropy in the activity of the enterprise: the content and the main approaches to evaluation
Keywords: ентропія; інформація; економічна ентропія; індивідуальний тезаурус; колективний тезаурус; середовище підприємства; entropy; information; economic entropy; individual thesaurus; collective thesaurus; enterprise environment; 338.24